The Emergence of Wage Coordination in the Central Western European Metal Sector and its Relationship to European Economic Policy - Vera Glassner; Toralf Pusch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
In the European Monetary Union the transnational coordination of collective wage bargaining has acquired increased importance on the trade union agenda. The metal sector has been at the forefront of these developments. This paper addresses the issue of crossborder coordination of wage setting in the metal sector in the central western European region, that is, in Germany, the Netherlands and Belgium, where coordination practices have become firmly established in comparison to other sectors. When testing the interaction of wage developments in the metal sector of these three countries, relevant macroeconomic (inflation and labour productivity) and sector-related variables (employment, export-dependence) are considered with reference to the wage policy guidelines of the European Commission and the European Metalworkers' Federation. Empirical evidence can be found for a wage coordination effect in the form of increasing compliance with the wage policy guidelines of the European Metalworkers' Federation. The evidence for compliance with the stability-oriented wage guideline of the European Commission is weaker. – – Seit Etablierung der Europäischen Währungsunion gewinnt die grenzüberschreitende Koordinierung von Lohnverhandlungen für die europäischen Gewerkschaften an Bedeutung. Insbesondere der Metallsektor nimmt dabei eine Vorreiterrolle ein. In diesem Beitrag werden die Effekte eines grenzüberschreitenden Koordinierungsnetzwerks im Metallsektor Deutschlands, der Niederlande und Belgiens untersucht. Bei den ökonometrischen Schätzungen werden makroökonomische und sektorspezifische Variablen verwendet und in Beziehung zur Lohnkoordinierungs-Leitlinie des Europäischen Metallgewerkschaftsbunds und der Europäischen Kommission gesetzt. Die empirischen Ergebnisse deuten auf einen Effekt des Lohnkoordinierungsnetzwerks hin, der im Einklang mit der Lohnkoordinierungs-Leitlinie des Metallgewerkschaftsbunds steht.
urn:nbn:de:101:1-20100706108
Keywords: J30; J51; E02; F55; L61; 330; wage coordination; metal sector; EMU; European economic policy; Lohnkoordination; Metallsektor; EWU; europäische Wirtschaftspolitik; Lohnpolitik; Tarifpolitik; Internationale wirtschaftspolitische Koordination; Metallindustrie; EU-Politik; Deutschland; Niederlande; Belgien